Welding and Joining of NiTi Shape Memory Alloys: A Review. (July 2017) - Oliveira, J.P.; Miranda, R.M.; Braz Fernandes, F.M.
Abstract: NiTi is an increasingly applied material in industrial applications. However, the difficulties faced when welding and joining is required, limits its broader use in the production of complex shaped components. The main weldability problems associated with NiTi are: strength reduction, formation of intermetallic compounds, modification of phase transformation and transformation temperatures, as well as, changes in both superelastic and shape memory effects. Additionally, NiTi is envisaged to be joined to other materials, in dissimilar joints with more complex problems depending on the other base material. Thus, intensive research in welding and its effects on the joints performance has been conducted since the early stages of NiTi. This paper presents a detailed review of welding and joining processes applied to NiTi, in similar and dissimilar combinations considering both fusion and solid-state processes. Since laser is the most studied and applied welding process, a special section is devoted to this technique.